The Influence of Emotional Demonstration on the Smoking Behavior of Junior High School (SMP) Adolescents in South Sinjai District, Sinjai Regency - Ramadhina, Vicky Milenia; Syafar, Muhammad; Thaha, Ridwan M. (International Journal of Statistics in Medical Research, 2023)
Purpose: This research aims to determine the influence of emo demonstrations on smoking behavior among junior high school (SMP) teenagers in Sinjai Selatan District, Sinjai Regency (Theory of Planned Behavior Approach). Method: This research used a research method, namely quantitative research using a quasi-experimental design with a nonequivalent control group design. The location of research and sampling was in the Sinjai Regency area. Samples were taken using the Accidental Sampling technique with as many as 250 respondents from the intervention and control groups. Analysis was carried out using the paired sample T test if the data was normally distributed and if the data was not normally distributed then the Wilcoxon test. Results: Show that knowledge (p=0.319 to p=0.689), attitude (p=0.032 to p=0.004), subjective norms (p=0.000 to p=0.087), and behavioral control (p=0.000 to p=0.003). Conclusion: It can be said that there is no change in knowledge and subjective norms in junior high school (SMP) teenagers in South Sinjai District regarding smoking behavior after being given emotional demonstration education and there is a change in attitude and behavioral control in junior high school (SMP) teenagers in Sinjai District South regarding smoking behavior after being given emotional demonstration education.